2017
DOI: 10.1186/s12864-017-3784-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic analyses reveal distinct biological functions for cold shock proteins (VpaCspA and VpaCspD) in Vibrio parahaemolyticus CHN25 during low-temperature survival

Abstract: Background Vibrio parahaemolyticus causes serious seafood-borne gastroenteritis and death in humans. Raw seafood is often subjected to post-harvest processing and low-temperature storage. To date, very little information is available regarding the biological functions of cold shock proteins (CSPs) in the low-temperature survival of the bacterium. In this study, we determined the complete genome sequence of V. parahaemolyticus CHN25 (serotype: O5:KUT). The two main CSP-encoding genes (VpacspA and VpacspD) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 68 publications
1
43
0
Order By: Relevance
“…The ABC transporter proteins, also known as highly conserved in ATP-binding sites proteins (Higgins et al, 1986), are found in all domains of life, and are mainly involved in the uptake of nutrients and micronutrients, extrusion of building blocks, and drug resistance by exporting certain toxic substances outside of the cell (Cuthbertson et al, 2010; Locher, 2016). Similar to the present findings, ABC transporters were found to be significantly inhibited in V. parahaemolyticus isolates with a mutation in the CSP gene cspA to compensate for the deficiency and protect the bacterium from low temperature induced damage (Zhu et al, 2017). Another report showed that V. parahaemolyticus ABC transporters demonstrated notable variation in response to acid and toxicity stress (Nydam et al, 2014; Sun et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…The ABC transporter proteins, also known as highly conserved in ATP-binding sites proteins (Higgins et al, 1986), are found in all domains of life, and are mainly involved in the uptake of nutrients and micronutrients, extrusion of building blocks, and drug resistance by exporting certain toxic substances outside of the cell (Cuthbertson et al, 2010; Locher, 2016). Similar to the present findings, ABC transporters were found to be significantly inhibited in V. parahaemolyticus isolates with a mutation in the CSP gene cspA to compensate for the deficiency and protect the bacterium from low temperature induced damage (Zhu et al, 2017). Another report showed that V. parahaemolyticus ABC transporters demonstrated notable variation in response to acid and toxicity stress (Nydam et al, 2014; Sun et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Selected salt resistance-associated genes were validated by qRT-PCR assay as described previously (Sun et al 2014;Zhu et al 2017). L. plantarum D31 and T9 strains were incubated in the MRS medium supplemented with 8% and 5% NaCl, respectively, and cell culture grown to logarithmic growth phase was harvested by centrifugation as described above.…”
Section: Quantitative Real-time Reverse Transcription Pcr (Qrt-pcr)mentioning
confidence: 99%
“…A 20-μl reaction volume contained 10 μl TB Premix Ex TaqTM II, 0.4 μl of each of the oligonucleotide primers (10 μmol), 0.4 μl of ROX Reference DyeII, 2 μl of cDNA template, and appropriate volume of sterile DNase/RNase-Free deionized water. All RT-PCR reactions were performed in a 7500 Fast Real-Time PCR System (Applied Biosystems, Foster City, CA, USA) under the following conditions: initial denaturation at 95°C for 10 min, followed by 40 cycles of denaturation at 95°C for 15 s, and primer annealing at 60°C for 60 s. The 16S rRNA gene was used as the reference gene, as previously described (Zhu et al 2017). The expression of the 16S rRNA gene in L. plantarum D31 and T9 strains grown to the logarithmic growth phase in MRS medium supplemented with no NaCl was used as a reference/baseline, respectively.…”
Section: Quantitative Real-time Reverse Transcription Pcr (Qrt-pcr)mentioning
confidence: 99%
“…In our prior studies, V. parahaemolyticus CHN25 strain (serotype: O5:KUT) was isolated, identified, and characterized ( Song et al., 2013 ; Sun et al., 2014 ; He et al., 2015 ; Zhu et al., 2017 ). The complete genome sequence of V. parahaemolyticus CHN25 contains 5,443,401 bp with 45.2% G+C content ( Zhu et al., 2017 ). Comparative genomic analysis revealed five prophage gene clusters in V. parahaemolyticus CHN25.…”
Section: Introductionmentioning
confidence: 99%